THE CONDITIONS FOR ACHIEVING STRATEGIC SUCCESS BY THE NATIONAL GUARD OF UKRAINE FORCES - Shmakov, О. М. (Honor and Law, 2019)
In the study, the list of missions and the nature of the National Guard of Ukraine are outlined for action in the strategic level and success in Guard performance. The Law of Ukraine “On the National Guard of Ukraine” [1] strengthened the functions of the Guards comparing with the internal troops of the Ministry of Internal Affairs of Ukraine; put forward the functions of ensuring state security. At the same time, it is being tried to deprive the National Guard of functions that are unusual for it. The National Guard has been authorized to protect the regional state administrations, which again belongs to the function of ensuring state security. It is considered the possibility of empowering the National Guard by the function to control the forces of territorial defense of Ukraine throughout the territory outside the zone of military operations. The expansion of the functions of the National Guard, its strengthening, including technical equipment, raised questions about its capabilities and a real role in ensuring the security of the state. Therefore, the concentration of the National Guard efforts in fulfilling the missions of ensuring state security itself, providing the possibility of functioning of the state authorities, determines the situation that the results of the National Guard activities may become strategic in the life of the state. The relevant issues are the identification of the conditions for achieving strategic success in the activities of the National Guard of Ukraine. The National Guard performs a major number of tasks in the field of security, not in the warfare. Therefore, the transfer of strategic ideas in the field of security requires taking into account general ideas about the essence of the known strategic provisions of military science in Ukraine. Usually military strategy is being considered with the level of the country, with the Armed Forces of Ukraine in general and other subjects of the Security and Defense Sector, Operations of United Forces, with strategic directions, campaigns, as well as with the states measures on strategic initiatives on establishing military and political alliances, with informational and psychological operations, mobilizing the population to protect the country. The strategic success of the National Guard depends on the scale of tasks on which it relies, and the possible negative consequences for the authorities that may occur in the event of the Guards failure. The objective of the National Guard is in the main - in the crisis of a socio-political nature to ensure the functioning of state authorities and local self-government bodies. The strategic success of the National Guard can also be attributed to the prevention of the seizure (undermining) of an embassy of a large foreign state developed in the economic (political) point of view; preventing the capture of an industrial facility if it is single in the country and meaningful for the state; preventing the seizure of nuclear power plants by a terrorist group when international resonance with unpredictable consequences for humanity can take place; preventing escape from custody in a politically important manner (in the case of the possibility of freely acting through the media and organizing further resistance to the authorities). In determining the possible level of actions of the National Guard (there is a strategic or operational nature of actions), it is necessary to predict the level of political negative consequences for the state in case of violation of social norms of behavior (conditions of activity of state objects), to check the estimations of the National Guard with the positions of state authorities. Strategic success in the actions of the National Guard takes place when the goal is achieved: in a crisis situation of a socio-political nature (emergency) the functioning of public authorities is ensured and protesters are forced to reduce their actions under conditions of state power.